2022
DOI: 10.3389/fpsyt.2022.854088
|View full text |Cite
|
Sign up to set email alerts
|

Alter Game: A Study Protocol on a Virtual “Serious Game” for Relapse Prevention in Patients With Gambling Disorder

Abstract: Cognitive behavioral therapy (CBT) is the most successful protocol in gambling disorder (GD) treatment. However, it presents some weaknesses, especially concerning relapse prevention (RP). RP is one of the most important therapeutic steps, aiming at managing cravings and to avoid future relapse increasing perceived self-efficacy. Encouraging results come from the blending of psychotherapy and virtual reality (VR), containing gambling cues. The goal of Alter Game (approved by the Ethical Commission, Prot. No. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Experimental studies have shown that mental imagery tasks can be used to promote satiation and habituation to the desired stimulus (Morewedge et al, 2010). In this regards, based on the relapse prevention (RP) model proposed by Marlatt and Gordon (1985), an innovative psychological treatment for GD by using Virtual Reality has been proposed (Giordano et al, 2022). The protocol is based on a virtual serious game, i.e., a game designed for purposes other than entertainment, to prevent relapse in gambling behaviour by increasing self-efficacy in managing craving and emotional states and by reducing perceived gambling craving.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that mental imagery tasks can be used to promote satiation and habituation to the desired stimulus (Morewedge et al, 2010). In this regards, based on the relapse prevention (RP) model proposed by Marlatt and Gordon (1985), an innovative psychological treatment for GD by using Virtual Reality has been proposed (Giordano et al, 2022). The protocol is based on a virtual serious game, i.e., a game designed for purposes other than entertainment, to prevent relapse in gambling behaviour by increasing self-efficacy in managing craving and emotional states and by reducing perceived gambling craving.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, another option for operationalizing relapse was proposed by asking the participants the following question directly: "Do you think that you have a gambling problem again?" Participants who answered "yes" were categorized as relapsers (Goudriaan, Oosterlaan, De Beurs, & Van Den Brink, 2008).…”
Section: Definitions Of Recovery Related To Gambling Severitymentioning
confidence: 99%
“…However, the clinical complexity of this case limited the possibility of attributing the improvement to the intervention with the serious game [74]. Furthermore, Giordano and colleagues [76] described another serious game treatment protocol (Alter Game) aimed at preventing gambling relapse, which employed biofeedback techniques measuring HR, HRV, skin conductance, and temperature to assess psychophysiological arousal in the face of gambling cues. In this vein, psychophysiological arousal is considered as an indirect measure of craving which, in turn, has been related to impulsivity in GD [77,78].…”
Section: Hrv Biofeedbackmentioning
confidence: 99%